Taxes and firm investment - Kerim Peren Arin; Kevin Devereux; Mieszko Mazur (University College Dublin, UCD Centre for Economic Research, 2021)
We investigate the firm level investment responses to narrative shocks to average personal and corporate tax rates using a universal micro dataset of publicly traded U.S firms for the post- 1962 period. By allowing for heterogeneous effects over the business cycle and accompanying monetary policy regime, as well as over firm-level characteristics, we show that : (i) corporate tax multipliers are negative overall, but this result is driven by smaller firms who face larger borrowing constraints, especially during high-unemployment periods or when the accompanying monetary policy is contractionary; (ii) while the magnitude and the significance of personal income tax multipliers are smaller on the aggregate, there is some evidence of positive personal tax multipliers in high-unemployment state by large (dividend-paying) firms, which is consistent with the recent literature.
hdl:10197/11868
Keywords: C33; C53; E62; G32; 330; Investment; taxation; fiscal policy; fiscal multiplier